2009
DOI: 10.1139/t09-019
|View full text |Cite
|
Sign up to set email alerts
|

Response of buried steel pipelines subjected to relative axial soil movement

Abstract: The performance of buried steel pipelines subjected to relative soil movements in the axial direction was investigated using full-scale pullout testing in a soil chamber. Measured axial soil loads from pullout testing of pipes buried in loose dry sand were comparable to those predicted using guidelines commonly used in practice. The peak values of axial pullout resistance observed on pipes buried in dense dry sand were several-fold (in excess of 2 times) higher than the predictions from guidelines; the observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 16 publications
2
27
0
1
Order By: Relevance
“…The results show a consistent agreement between the estimated and calculated values with a maximum difference of 6%. Wijewickreme et al [39] suggested that when using Eq. (1) to find the axial resistance in compacted sand, K value should be considered within a range between K 0 and 2.5.…”
Section: Validation Of the Proposed Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results show a consistent agreement between the estimated and calculated values with a maximum difference of 6%. Wijewickreme et al [39] suggested that when using Eq. (1) to find the axial resistance in compacted sand, K value should be considered within a range between K 0 and 2.5.…”
Section: Validation Of the Proposed Expressionmentioning
confidence: 99%
“…[2,7,10,18,21,25,26,[37][38][39]. Roy et al [33] used finite element (FE) analysis to model soil-pipe interaction in dense sand subjected to lateral ground displacements.…”
mentioning
confidence: 99%
“…The u is used to express the ultimate axial friction coefficient and determined based on ultimate axial resistances using Eqs. (2), (3) and (5). The r is used to express the residual axial friction coefficient and determined based on residual axial resistances using Eqs.…”
Section: Axial Friction Responsesmentioning
confidence: 99%
“…The subsea pipelines in soft clays generally operate at relatively high pressures and temperatures during transporting oil or gas. These conditions require pipeline to be designed to buckle in a controlled manner during its service life, especially the phase of startup and shutdown [1][2][3][4]. The axial friction resistance of pipelines has a significant impact on the axial buckling design of subsea pipelines in soft clays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation